CHARACTER DEVELOPMENT OF STUDENTS THROUGH ISLAMIC EDUCATION LEADERSHIP - Rivaldi, Muhammad; Ramadhan, Narendra Jumadil Haikal (Al-Masail: Journal of Islamic Studies, 2024)
Leadership in Islamic education institutions has a very important role in shaping the character of students in accordance with Islamic values. Leaders in Islamic education institutions are not only responsible for administrative management, but also for ensuring that character education goals are achieved. This article examines the role of leadership in Islamic education institutions, especially pesantren and madrasah, in developing learners' character through an approach based on integrity, morality, responsibility, vision, exemplary, faith, and social. This research uses a qualitative method based on literature review by examining various literature from relevant academic sources. The results show that effective leadership guided by Islamic values can create an educational environment conducive to the development of moral and spiritual character of students, so that they can face the challenges of globalization and social change. This article makes a theoretical contribution to Islamic educational leadership and offers practical insights to improve the quality of character education in Islamic educational institutions